Agrarian question and education of geography: representations on agribusiness in Chapada do Apodi, Ceará - Lima, Maria Tamires Teotônio; Cavalcante, Leandro Vieira (Geosaberes; Vol 10 No 22 (2019): Sept - DecDO - 10.26895/geosaberes.v10i22.753, 2019)
This paper seeks to discuss the relation between the agrarian question and the teaching of Geography in the Chapada do Apodi - Ceará, analyzing the representations about the expansion of agribusiness in the region. The methodology was structured in the bibliographical survey and in the realization of a drawing workshop focused on the understanding of the representation of the agrarian question by the students, specifically the agribusiness. With the research, it was verified that it is fundamental that the agrarian question is approached in the schools of basic education, mainly those they experience directly or indirectly the impacts arising from the agribusiness, to highlight the teaching of Geography as an instrument that provides students with a critical and emancipatory awareness that can apprehend and to problematize your reality.